Role of circular RNAs in DNA repair - Francisco Alejandro Lagunas-Rangel (RNA Biology)
Circular RNAs (circRNAs) exhibit a wide range of activities that allow them to participate in numerous cellular processes and make them relevant in a variety of diseases. In this regard, a key process in which circRNAs are involved, and which is the focus of this article, is DNA damage repair (DDR). This study aims to illustrate how circRNAs influence different DNA repair pathways, with particular emphasis on the underlying mechanisms. In addition, the potential medical applications of this knowledge are discussed, particularly in the diagnosis, prognosis and treatment of diseases. In this sense, circRNAs were found to play a crucial role in DNA repair processes by regulating the expression and activity of proteins involved in various DNA repair pathways. They influence the expression of DNA repair proteins by interacting with their mRNAs, sponging miRNAs that target these mRNAs, regulating transcription factors that bind to their promoters, modulating upstream signalling pathways, and affecting mRNA translation. Furthermore, circRNAs regulate the activity of DNA repair proteins by interacting directly with them, sequestering them in specific cellular compartments and controlling activation signalling or upstream DDR signalling.